A descriptive analysis of caesarean section rate in a tertiary care hospital according to Robson’s criteria - Bhattacharjee, Surjyatapa; Negi, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: There has been a rapid increase in rates of caesarean section (CS) in the past decade, leading to increased complications not only in the current pregnancy but also in subsequent pregnancies. Hence Robson’s ten group classification has been used to analyse the indications, scrutinize the rate of CS so that only obstetrically indicated CS are carried out. Methods: The cross-sectional study was carried out for a period of 6 months from 1/7/2019 to 31/12/2019 at Silchar medical college and hospital. All the women ≥28 weeks who delivered during the said period were taken into account. The data was then regrouped according to Robson’s classification. Results: The overall CS rate in our study was 38.09%. Most of the women who underwent CS belonged to age group 20-24 years (49%). 43.26% were nullipara and 91.86% females were term. On analysis of CS according to Robson’s classification, it was observed that group 1 (35.14%) constituted the largest number of women. However, group CS rate was highest in group 9 (100%). Group 5 made the greatest relative (38.83%) as well as absolute contribution (14.79%). Fetal compromise seems to be the leading cause for primary CS. Conclusions: The CS rates in our study have been found to be comparatively higher as the hospital is a tertiary referral centre. Since the maximum contribution has been made by the previous CS group, the rate of primary CS should be reduced and more vaginal birth after CS may be encouraged.